2020
DOI: 10.1074/jbc.ra120.013102
|View full text |Cite
|
Sign up to set email alerts
|

The acetyltransferase Eco1 elicits cohesin dimerization during S phase

Abstract: Cohesin is a DNA-associated protein complex that forms a tripartite ring controlling sister chromatid cohesion, chromosome segregation and organization, DNA replication, and gene expression. Sister chromatid cohesion is established by the protein acetyltransferase Eco1, which acetylates two conserved lysine residues on the cohesin subunit Smc3 and thereby ensures correct chromatid separation in yeast (Saccharomyces cerevisiae) and other eukaryotes. However, the consequence of Eco1-catalyzed cohesin acetylation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Mechanistically, the acetylation of Smc3 inhibits both the ATPase activity of cohesin and conformational changes (Camdere et al, 2018). Recently, it has been suggested that acetylation also induces cohesin dimerization (Shi et al, 2020a). Either way, we suggest that, as a result of the acetylation, cohesin loop extrusion is fully turned off, likely by modifying the ATPase activity at the SMC head.…”
Section: Molecular Switches For Turning Off Loop Extrusionmentioning
confidence: 71%
“…Mechanistically, the acetylation of Smc3 inhibits both the ATPase activity of cohesin and conformational changes (Camdere et al, 2018). Recently, it has been suggested that acetylation also induces cohesin dimerization (Shi et al, 2020a). Either way, we suggest that, as a result of the acetylation, cohesin loop extrusion is fully turned off, likely by modifying the ATPase activity at the SMC head.…”
Section: Molecular Switches For Turning Off Loop Extrusionmentioning
confidence: 71%
“…After proofreading cohesin stops at the opposite side of a TAD loop and then induces proofreading of SAT domain by another complex (SMS5/6) in a relay race mechanism. However, it should be taken into account that 20% of cohesin (SMC complex) does not move; it forms cohesin dimers that keep sister chromatids together (Shi et al, 2020) ("cohesin" in a true sense).…”
Section: Structure Of Tad Anchorsmentioning
confidence: 99%
“…Recently, the inter-allelic complementation between defective Scc1 and Smc3 alleles has provided evidence that multiple cohesin subunits can interact with each other on the chromatin [193,194]. Indeed, many biochemical studies have confirmed that cohesin can form clusters or dimers in vivo [195,196]. The exact mechanism of action is still debated (reviewed by [190]).…”
Section: Sister Chromatid Cohesionmentioning
confidence: 99%